A greenstick fracture of the patella: a unique fracture in CP crouch gait. (22nd May 2013) - Elhassan, Yahya; Mahon, Judy; Kiernan, Damien; O Brien, Tim
Abstract : We report a greenstick fracture of the patella in an ambulant boy with diplegic cerebral palsy (CP). The boy was known to have knee crouch which was documented in our gait laboratory. Greenstick fractures usually occur in the long bones of children and are caused by a bending force. This is the first report of a patellar greenstick fracture and provides a unique insight into the propagation of patellar fractures in CP crouch.